Racism/Anti-Racism, Precarious Employment, and Unions - Das Gupta, Tania (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
[The author] is concerned with the way the mainstream labour movement has historically treated non-white workers in precarious employment and the role of history in shaping contemporary practices. Das Gupta's offers a qualitative analysis of the perceptions and experiences of labour activists of colour and of alternative advocacy strategies for building more inclusive resistance movements. --From editor's introductory chapter, p. 38.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment